Exploring the applicability of the Semantic Web for discovering and navigating Australian Indigenous knowledge resources - Corn , Aaron; Wantarri Jampijinpa Patrick , Steven (Archives & Manuscripts, 2019)
Semantic Web ontology files can be flexibly programmed to delineate metadata relationships in machine-readable formats to create relational pathways for discovering resources both on and off the Internet. There is a global community of Semantic Web developers and users across a broad multi-disciplinary range of interests who create and share extensible open-source ontologies. In this article, the author will explore the functionality of Semantic Web techniques for representing the ontologies of relatedness through kinship that typically underpin Australian Indigenous knowledge systems, and investigate their potentials for meeting persistent demands among leading Australian Indigenous collections creators and users to be able to search and discover their hereditary knowledge resources in ways that reflect and reinforce their enduring cultural values, ways of knowing and rights-management concerns.